2019
DOI: 10.1017/s0031182019000441
|View full text |Cite
|
Sign up to set email alerts
|

Participation ofTrypanosoma cruzigp63 molecules on the interaction withRhodnius prolixus

Abstract: Trypanosoma cruzi is the causative agent of Chagas disease, a vector-borne disease. The parasite molecules involved in vector interaction have been little investigated. Metallopeptidases and gp63 molecules have been implicated in parasite adhesion of several trypanosomatids to the insect midgut. Although gp63 homologues are highly expanded in the T. cruzi genome, and are implicated in parasite–mammalian host interaction, its role in the insect vector has never been explored. Here, we showed that divalent metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(75 reference statements)
1
9
0
Order By: Relevance
“…Cuevas et al have reported that the Tcgp63-I, is expressed in the different parasite stages, but a very low metalloprotease activity in epimastigotes extracts was observed by zymography, using 250 × 10 6 parasites [ 48 ]. In agreement, Rebello et al also observed gp63 gelatinolytic activity in epimastigotes stage extracts [ 49 ]. It is important to note, that the maximum number of circulating parasites of samples that we analyzed, were 4 × 10 6 mL −1 (Cvd strain) and 3,5 × 10 6 mL −1 (Ac strain), ( Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Cuevas et al have reported that the Tcgp63-I, is expressed in the different parasite stages, but a very low metalloprotease activity in epimastigotes extracts was observed by zymography, using 250 × 10 6 parasites [ 48 ]. In agreement, Rebello et al also observed gp63 gelatinolytic activity in epimastigotes stage extracts [ 49 ]. It is important to note, that the maximum number of circulating parasites of samples that we analyzed, were 4 × 10 6 mL −1 (Cvd strain) and 3,5 × 10 6 mL −1 (Ac strain), ( Fig.…”
Section: Discussionsupporting
confidence: 78%
“…The surface protease gp63 is a very well-known protease from T. cruzi important for host cell infection ( Kulkarni et al., 2009 ) and presents metalloprotease activity ( Cuevas et al., 2003 ). In our gelatin zymography assays, we observed gelatinolytic activity that could be related to the presence of gp63, since the negative bands presented a size between 45 and 66 kDa ( Rebello et al., 2019 ).…”
Section: Discussionmentioning
confidence: 88%
“…The 63 kDa glycoprotein (gp63), another widely studied Leishmania virulence factor, encoded by a multigene family highly expanded in T. cruzi genome ( El-Sayed, 2005 ), may contribute to the parasite’s virulence in the insect stage via its metalloprotease activity ( Cuevas et al., 2003 ). A study has also shown the participation of gp63 in the parasite’s adhesion to Rhodnius prolixus midgut via assays using divalent metal chelators or anti-Tcgp63-I antibodies caused an impaired T. cruzi adhesion to the vector midgut ( Rebello et al., 2019 ).…”
Section: Virulence Factors In Insectsmentioning
confidence: 99%
“…Despite it has been hard to obtain direct evidence of the protein’s nutritional role in insects, the adhesion events have been widely demonstrated both in monoxenous trypanosomatids, e.g., Crithidia guilhermei ( D’Avila-Levy et al., 2006a ), Leptomonas spp. ( Pereira et al., 2009 ), Angomonas deanei ( D’Avila-Levy et al., 2008 ) and Herpetomonas muscarum ( Nogueira de Melo et al., 2006 ); and dixenous trypanosomatids, e.g., Phytomonas serpens ( D’Avila-Levy et al., 2006b ), T. cruzi ( Rebello et al., 2019 ) and Leishmania spp. ( Soares et al., 2017 ).…”
Section: Virulence Factors In Insectsmentioning
confidence: 99%